(untitled) ("Conference on Universal Science Research 2023", 2023)
This article is the current era, when societies are actively integrating with each other, the development of information technology, communication, technologies is becoming globalized, in a word, the era of globalization and information societies are settling down, and it is increasingly vital for us to study it comprehensively in the period when the settlement of the information society is accelerating. is becoming a necessity, and the study of the history and causes of the origin of such a society is one of the main issues on the agenda.